1995
DOI: 10.1002/cber.19951280209
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoordinate Carbon in Trigoldbis(silyl)methanium Cations

Abstract: The reactions of organolithium compounds of the type (R3Si)2CHLi (R3 = Me3 or Me2Ph) with the gold(I) complex Ph3PAuCl afford the monoaurated bis(silyl)methanes (R3Si)2‐ CHAuPPh3 (1a, b) in high yield. These compounds are converted into complex salts with hypercoordinate methanium cations {(R3Si)2C[Au(PPh3)]3}+BF−4 (3a, b) by treatment with {[(Ph3P)Au]3O}+ BF−4. In the reaction mixtures small amounts of the neutral dinuclear intermediates {(R3Si)2C[Au(PPh3)]2} (2a, b) have been detected and characterized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…The precipitate was filtered and washed three times with cold water and dried under vacuum to afford tdmegb (1.14 g, 2.2 mmol, 74 %) as a white powder. C 26 X-ray Crystallographic Study: Suitable crystals were taken directly out of the mother liquor, immersed in perfluorinated polyether oil, and fixed on top of a glass capillary. Measurements were made on a Nonius-Kappa CCD diffractometer with low-temperature unit using graphite-monochromated Mo-K α radiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitate was filtered and washed three times with cold water and dried under vacuum to afford tdmegb (1.14 g, 2.2 mmol, 74 %) as a white powder. C 26 X-ray Crystallographic Study: Suitable crystals were taken directly out of the mother liquor, immersed in perfluorinated polyether oil, and fixed on top of a glass capillary. Measurements were made on a Nonius-Kappa CCD diffractometer with low-temperature unit using graphite-monochromated Mo-K α radiation.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the tdmegb/[AuClPPh 3 ]/CH 3 CN reaction mixture adopted a bright yellow colour, and upon cooling of the mixture to room temperature yellow crystals precipitated. Spectroscopic data in alliance with an XRD analysis of the crystalline material revealed the formation of the new Au (6) pm is realized, [26] being close to the values in [AuPh(PPh 3 )] and related molecules in which an sp 2 hybridized carbon is bound to Au I (around 205 pm). [27,28] A significantly longer Au-C bond [208.7(3) pm] is found in the Au complex arising from coordination of 1,3-dimethyl-2-methylene-imidazoline to the [Ph 3 PAu] fragment (see Scheme 2).…”
mentioning
confidence: 85%
“…but instead underwent a SiC coupling reaction with hydride elimination to give a branched carbon/sili con frame (6). M etallation of (M e2PhSi)2CHBr (1) was found to proceed normally, however, and the resulting (M e2PhSi)2CHLi reagent could finally be used for step-wise auration with Ph3PAu+ reagents [15].…”
Section: Resultsmentioning
confidence: 99%
“…(HM e2Si)2CHBr (5) has been obtained by methods successfully employed already for the preparation of other highly silylated hydrosilane molecules [7][8][9]. From (M e2PhSi)2CH Br (1) the phenyl groups can be removed quantitatively by selective protodesilylation [10,11] with triflic acid (eq.…”
Section: Synthesis O F the Compoundsmentioning
confidence: 99%
“…Depending on the substitution pattern of the monomers, different kinds of cross-linking are to be expected, which are leading to simple oligomers, rings, chains, or polydimensional networks [1]. Simple poly(silyl)-arenes bearing solely hydrogen at the silicon sub stituents were largely unknown until some very re cent studies, which have shown the way to at least a few of the possible poly(silyl)benzenes and their isomers [2], Following our own work on poly(silyl)alkanes [3][4][5][6][7], -alkenes [8][9][10], -alkynes [11,12], and -arenes [12], including hexa(silyl)benzene [13] and l,8-di(silyl)naphthalene [14], we now report the first synthesis of the title compounds, the silicon analogue of o-xylene and one of its brom inated derivatives.…”
mentioning
confidence: 99%